How much training do English male academy players really do? Load inside and outside of a football academy - Johnson, D. M.; Cumming, S. P.; Bradley, B.; Williams, S. (International Journal of Sports Science & Coaching, 2023)
To date, no studies have investigated the loads undertaken by elite youth footballers outside of their academy commitments. This study aimed to understand the load of English male academy football players' activity both inside and outside of the academy, as well as, how this load varies between age groups and days. Fifty-two male academy footballers were asked to record the duration, intensity and mode of moderate to vigorous physical activity undertaken outside of their academy training. These data were then combined with session Rating of Perceived Exertion load undertaken inside the academy over the corresponding period. Data were analysed using linear mixed models. The coefficient of variation (CV) was the between-subject standard deviation as a percentage of the mean. The variation of activity types players undertake outside the academy reduced with age. There was no significant difference in the `outside of academy` load between age groups, but there was a significantly greater CV in the Under 15/16 (U15/16) group (CV = 164%) compared to the U12 (CV = 107%) and U13/14 (CV = 119%) age groups (P = 0.001). For the U12 group, there were no significant between-day differences in load outside of the academy or the combined (inside and outside) load. For the U13/14 and U15/16 groups, there were significant between-day differences in load outside of the academy, as well as, significant between-day differences in the combined load. Practitioners should consider how activities undertaken by players outside of the academy setting contribute to the weekly load periodisation and should modify their training schedules accordingly.